2008
DOI: 10.1111/j.1567-1364.2007.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecm11 protein of yeastSaccharomyces cerevisiaeis regulated by sumoylation during meiosis

Abstract: Damaged regulation of the small ubiquitin-like modifier (SUMO) system contributes to some human diseases; therefore, it is very important to identify the SUMO targets and to determine the function of their sumoylation. In this study, it is shown that Ecm11 protein in Saccharomyces cerevisiae is modified by SUMO during meiosis. It is known that Ecm11 is required in the early stages of yeast meiosis where its function is related to DNA replication and crossing over. Here it is shown that the level of Ecm11 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…From the microarray hybridization data available in the Stanford Genome Database (SGD; http://www.yeastgenome.org/), it is apparent that the ECM11 transcript does not oscillate during the cell cycle, but is significantly elevated during meiosis. It was confirmed that the level of protein Ecm11 is in accordance with the mRNA: the level of Ecm11 protein is low in mitosis, but high in meiosis (Zavec et al, 2008). The highest level of Ecm11 is in the earlymiddle phase of sporulation.…”
Section: Ecm11 Yeast Protein With a Role In Replication And Recombinsupporting
confidence: 58%
See 2 more Smart Citations
“…From the microarray hybridization data available in the Stanford Genome Database (SGD; http://www.yeastgenome.org/), it is apparent that the ECM11 transcript does not oscillate during the cell cycle, but is significantly elevated during meiosis. It was confirmed that the level of protein Ecm11 is in accordance with the mRNA: the level of Ecm11 protein is low in mitosis, but high in meiosis (Zavec et al, 2008). The highest level of Ecm11 is in the earlymiddle phase of sporulation.…”
Section: Ecm11 Yeast Protein With a Role In Replication And Recombinsupporting
confidence: 58%
“…The Ecm11 protein has two lysine residues, K5 and K101, with a corresponding surrounding sequence IKTE that could accept SUMO. It was confirmed by immunoprecipitation that Ecm11 is sumoylated during meiosis and that Ecm11 interacts with SUMO covalently (Zavec et al, 2008). The majority of Ecm11 protein in the cell is sumoylated during meiosis.…”
Section: Ecm11 Is Modified By Sumo During Meiosis 831 Sumoylation Ssupporting
confidence: 49%
See 1 more Smart Citation
“…Second, SUMO-1, one of the four members of SUMO family, colocalizes with the SC only at synapsed regions; moreover, both lateral and central components are SUMOylated in human cells (Brown et al 2008). Third, Ecm11, a member of the SC central region of budding yeast, is SUMOylated, and this modification is important for the assembly of the Zip1 traverse filaments along homologs but is dispensable for their assembly into polycomplexes, suggesting a specific role in promoting chromosome-associated SC polymerization (Zavec et al 2008;Humphryes et al 2013). However, the precise role of SUMO for SC formation remains to be defined (see discussion in Watts and Hoffmann 2011).…”
Section: Structurementioning
confidence: 99%
“…Therefore, it appears that sumoylation is important both in the early stages of chromosome pairing/homology sorting and later on in the assembly of the mature SC Nottke et al Page 14 The proteins are subdivided into functional categories of DSBR (Double-strand break repair), Structural and Chromosome Segregation, and Transcriptional based on published literature. Identification of sumoylation and description of meiotic roles are consolidated from the Saccharomyces Genome Database (SGD) and the following primary sources: (Branzei et al 2006;Cheng et al 2006;Denison et al 2005;Hannich et al 2005;Panse et al 2004;Sacher et al 2006;Zavec et al 2008) …”
Section: Discussionmentioning
confidence: 99%